1575 Lumbar Puncture(LP) in Infants and Children with Suspected Meningitis: Regional Trends over 15 Years. (October 2012) - Barsoum, Z; Kieran, E; Powell, J; Barrett, N; Connell, NO; Philip-Limerick, RK
Abstract : Background and Aims: Lumbar puncture (LP) has been long considered a useful tool to assist in the diagnosis of meningitis. We aim to study the trends of successful LPs in an Irish Regional hospital and to further analyse, timing of LP, microbiological and serological positive yield and the potential impact on treatment. Methods: A retrospective analysis of laboratory data of all successful LPs for suspected meningitis among the 0–15 year age group was performed from July 1996 to December 2010 at University Hospital-Limerick. Repeat studies and samples from the Regional Maternity hospital were separately analysed.CSF studies for other conditions were excluded.HIPE data on meningitis admissions and supportive laboratory data were collated. Hospital Audit commitee approval was obtained. Results: 1487 successful LPs were performed from 1996 to 2010.Of these 646 procedures were performed from1996 to 2000 and 463 samples obtained from 2001 to 2005.Only 378 LPs were performed from 2006 to 2010.Of those with CSF analysed, 967(65%) were 2 years or younger. 53% of LPs were performed at night time. Only 18 patients had bacterial meningitis confirmed on CSF(1.2%) from 2001 to 2010 and 60% were infants.LP was performed before the use of antibiotics in 15% of cases. Nisseria meningitidis B and Stryptococcus pneumoniae were the leading causes of meningitis (38%&27% respectively).Among those with confirmed meningitis on CSF, serum PCR was positive in 77% while CSF PCR was positive in 100% of cases. Conclusion: Incidence of bacterial meningitis is decreasing mainly due to effective vaccination programmes.LP, even in the post vaccination era with early use of emperical antibiotics, still has a role in the diagnosis of meningitis.